Exploiting music structures for digital libraries. - Ehmann, A; Bay, M; Downie, J; Fujinaga, I; Roure, D (ACM, 2011)
This demonstration presents a music structure-based audio/visual interface for the navigation of very large scale music digital libraries. This work is a product of the Structural Analysis of Large Amounts of Music Information (SALAMI) project. © 2011 Authors.